Step 1: {Determine stopping condition}
The angular velocity is given as:
\[
\omega = \alpha - \beta t
\]
The body stops when \( \omega = 0 \), so:
\[
0 = \alpha - \beta t
\]
Solving for \( t \):
\[
t = \frac{\alpha}{\beta}
\]
Step 2: {Use kinematic equation for angular motion}
The equation:
\[
\omega^2 = \omega_0^2 + 2\beta \theta
\]
Substituting \( \omega_0 = \alpha \) and \( \omega = 0 \):
\[
0 = \alpha^2 - 2\beta \theta
\]
Step 3: {Solve for \( \theta \)}
\[
\theta = \frac{\alpha^2}{2\beta}
\]
Thus, the correct answer is (A) \( \frac{\alpha^2}{2\beta} \).